EŞECUL – CEA MAI MARE PARTE A INOVAŢIEI - KULIKOVSKI, Conf. univ. dr. director, Departamentul studii şi cercetări, Lidia (BIBLIOPOLIS, 2020)
The workshop „The failure – the first step for innovation” within the framework of the Library Cafe „Chindii profesionale” (Professional meeting at sunset) has the objective to understand the role of failure in professional activity. Talking about failure is an ambitious initiative of the Municipal Library and its branches. The idea is to dream nice dreams, more colorful, to change the way of thinking about our activities, the way of our evaluating and evaluating of ourselves. This is beyond anything we have tried before. More and more people recognize the impossibility to drive innovation without understanding the failure. The opening to failure, the use of failure in collaboration, adaptation, can change our potentional to innovate and solve our most difficult problems. The potential to change the way of how the library and the librarians react to failures is building by inviting people to share the failures by creating safe spaces to talk about and learn from the failures in order to increase the innovation and learning in every place of the library.